Pengaruh Pembiayaan Murābahah terhadap Peningkatan Usaha Anggota Koperasi Mitra Manindo Kantor Kas Siabu - Tri Surya; Muhammad Isa; Aliman Syahuri Zein (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2020)
Abstract The background of the problem in this study is the difference in income between customers who use murābahah financing at the Koperasi Mitra Manindo Siabu cash office. The research objective was to determine the effect of murābahah financing on increasing the business of members of the Koperasi Mitra Manindo Siabu cash office. This research used quantitative method. The data source used is primary data. The data collection technique used was a questionnaire, with a sample size of 86 customers. The analytical tool used is the validity and reliability test, normality test, descriptive statistics, simple regression analysis, hypothesis testing (t-test), test the coefficient of determination R2. By using the SPSS Version 22.0 program. The r-square value of 0.194 means that 19.4% of the Murabahah financing variable can explain the business improvement variable in the Mitra Manindo cooperative, Siabu cash office, while the remaining 80.6% is influenced by other variables not discussed in this model. Based on the t-test, it is known that murābahah financing affects increasing the business of members of the Koperasi Mitra Manindo Siabu cash office.